Akselerasi UMKM Halal melalui Peningkatan Literasi Halal - Surifah; Fran Sayekti; Lilis Endang Wijayanti; Inon Listyorini; Erna Fitri Komariyah; Evada Rustina; Ifah Rofiqoh (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2026)
Halal literacy assistance is important to support halal snack centers in Yogyakarta City. Three basic instruments of halal literacy used by the service team are knowledge and ability to recognize halal labels, halal awareness, and halal food ingredients. Before the assistance was carried out, the service team gave a pre-test and after the assistance was carried out, a post-test was carried out. The test results using the level of respondent achievement regarding halal knowledge, partners were very good and there was an increase after the assistance was carried out. For the departure of MSMEs, the borrower needs to provide some assistance on other materials related to the needs of MSMEs.